Fatty Acid Diets: Regulation of Gut Microbiota Composition and Obesity and Its Related Metabolic Dysbiosis - Machate, David Johane; Figueiredo, Priscila Silva; Marcelino, Gabriela; Guimarães, Rita de Cássia Avellaneda; Hiane, Priscila Aiko; Bogo, Danielle; Pinheiro, Verônica Assalin Zorgetto; Oliveira, Lincoln Carlos Silva de; Pott, Arnildo (International journal of molecular sciences, 2020)
Long-term high-fat dietary intake plays a crucial role in the composition of gut microbiota in animal models and human subjects, which affect directly short-chain fatty acid (SCFA) production and host health. This review aims to highlight the interplay of fatty acid (FA) intake and gut microbiota composition and its interaction with hosts in health promotion and obesity prevention and its related metabolic dysbiosis. The abundance of the Bacteroidetes/Firmicutes ratio, as Actinobacteria and Proteobacteria species are associated with increased SCFA production, reported high-fat diet rich in medium-chain fatty acids (MCFAs), monounsaturated fatty acids (MUFAs), and n–3 polyunsaturated fatty acids (PUFAs) as well as low-fat diets rich in long-chain fatty acids (LCFAs). SCFAs play a key role in health promotion and prevention and, reduction and reversion of metabolic syndromes in the host. Furthermore, in this review, we discussed the type of fatty acids and their amount, including the administration time and their interplay with gut microbiota and its results about health or several metabolic dysbioses undergone by hosts.